PENINGKATAN MINAT BACA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PLAY-THINK-PAIR-SHARE DI SDN 19 NAN SABARIS - Zakirman Zakirman (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
Learning at the Elementary School level is dominated by information gathering activities to build students' knowledge. The concept of learning is related to constructivist learning theory and requires students to have a high reading interest. Based on interviews with SDN teachers 19 Nan Sabaris revealed the findings that students' reading interest was still low, this was confirmed by the fact that the learning methods that were often used were lectures. The purpose of this study was to see the effect of using the Play-Think-Pair-Share model to increase students' reading interest. This type of research is quasi-experimental, with a sample of fifth grade students at SDN 19 Nan Sabaris in the 2018/2019 school year. The data collection instrument used is the student interest reading assessment sheet, with the data analysis technique chosen is paired sample t-test. Based on the results of data analysis it was found that the sig 2.tailed value was 0.0000 smaller than the value of ? = 0.05, so it can be concluded that there were significant differences in reading interest between before and after the use of Play-Think-Pair-Share models in elementary school learning.